The Role of Strategic Management in Implementing Total Quality Management Standards: An Analytical Study of Educational Institutions in Libya (Comprehensive Journal of Science, 2026)
This study investigated the role of strategic management in implementing Total Quality Management (TQM) standards within educational institutions, It aimed to explore and analyze the nature of the relationship between these two concepts, as well as the key TQM standards in Libyan educational institutions and their corresponding strategic options, Employing a descriptive-analytical methodology, the study reached several key findings, most notably: the relationship between strategic management and TQM in Libyan educational institutions is an organic, complementary one; strategic management provides the executive tools and options, while TQM establishes performance standards and indicators, Furthermore, the results revealed a fundamental shift in the quality system within the Libyan education sector toward outcomes-based assessment, This shift necessitates the adoption of strategic choices focused on refining students' behavioral skills and extracurricular activities, The study emphasized that providing technical and physical support resources—such as laboratories, internet connectivity, and facilities—is an essential strategic pillar to ensure the continuity of the educational process and the attainment of national and international accreditation requirements.
Keywords: Strategic Management - Total Quality Management (TQM) Standards